Courting Disorder: Some Thoughts on Community Courts - Anthony C. Thompson (Washington University Journal of Law & Policy, 2002)
This Essay will use empirical and anecdotal data as well as existing literature on community courts to evaluate the effectiveness of these courts in achieving their stated objectives. In so doing, this Essay does not purport to evaluate all types of community courts. Nor will it attempt to provide an in-depth analysis of all the issues that surround the history, establishment, design, and operation of community courts. Rather, this Essay will identify certain representative problems that inevitably occur in these courts and will examine the extent to which the conflicts inherent in their operation prevent these courts from achieving their aims. Part I briefly examines the history of drug courts and explores questions about their management and operation. Part II traces the progression from drug courts to the broader notion of community courts and questions the assumption that the methodology used in drug courts should be employed in other types of courts. Part III sets out an appropriate research agenda for determining whether community courts should continue to flourish.
Keywords: Drug courts; Judicial reform; Neighborhood justice centers; States; United States; Neighbourhood justice centres